Dynamics of heart rate variability in rats with streptozotocin-induced diabetes - Maria P. Morozova; Svetlana A. Gavrilova; Evgeniy V. Ivanov; Anna M. Gorbacheva; Ekaterina M. Rzhavina; Aleksey K. Erdyakov; Zera N. Dzhemilova; Ekaterina V. Artemova; Alla Y. Tokmakova; Vladimir B. Koshelev; Gagik R. Galstyan (Сахарный диабет)
Background: Diabetes mellitus (DM) has a negative impact on all organs. This is due to insufficiency of blood supply and the disruption of the trophic function of the nervous system. One of the most serious complication of DM is diabetic foot caused be vascular and neurological reasons. Correction of vascular disorders is effectively treated by modern therapeutic approaches, but the damage of nervous system has been studied insufficiently. Aims: To investigate the dynamics of damage to the vegetative nervous system on the laboratory model of DM. Materials and methods: DM in rats was induced by injection of streptozotocin at a dose of 65 mg/kg in citrate buffer (DM group). The control group of rats received a citrate buffer equivalent (CB group). Rats with DM were given a maintenance therapy with insulin in a dose of 2 units/kg/day. On 42 days of experience, a round wound with a diameter of 2 cm on the back of the animals was observed. Before the DM simulation, then on the 42, 50, 58 and 66 days of its development, an electrocardiogram (ECG) was recorded in the rats at a frequency of 2 kHz digitising in a state of calm wakefulness and after cold exposure. For 5 minutes ECG fragments, heart rate and heart rate variability (HRV) in the temporal domain were calculated, characterising: 1) the total heart rate variability (tHRV) according to SDRR, SDHR, KVRR and KVHR; 2) the effect of the parasympathetic department of the autonomic nervous system (aANS) for RMSSD and pNN3; 3) the contribution of the sympathetic department of the ANS (sANS) by SDAvgRR, SDAvgHR. The spectral parameters were estimated in the frequency domain: the total power of the spectrum is TR (range: 0–2.5 Hz), the powers in the low and high frequency ranges are LF (range: 0.2–0.8 Hz) and HF (range: 0.8–2.5 Hz) LF/HF. Weekly, the tail withdrawal time was measured in a temperature pain test (55°C). Results: During the development of diabetes, the level of glucose in the blood increased 4–7 times compared with the normal level. The reaction time of the pain test in rats with DM increased by 20%–30% at the end of the experiment. At 42 days, the development of bradycardia (267 beats/min) was observed in rats with DM. The indicators of tHRV decreased by a factor of 2 due to a decrease in the contribution of sANS. The reaction to CP in the SD group differs from the norm by the severity of the individual components of the HRV structure, which indicates functional denervation of the heart and the development of diabetic neuropathy. Conclusions: As the diabetes progressed, signs of neuropathy were observed. The overall HRV parameters decreased, the ratio of the contributions of sANS and pANS to the regulation of heart rate changed, and the temperature sensitivity decreased.